Primary entropion in persian cats - Laus, José Luiz [UNESP]; Vicenti, Felipe Antônio Mendes [UNESP]; Talieri, Ivia Carmen [UNESP]; Jorge, Adriana Torrecilhas [UNESP]; Bolzan, Aline Adriana [UNESP] (Universidade Federal de Santa Maria, 1999)
Entropion is defined as the inward rolling of the eyelid margin in which the eyelashes and eyelid hair (frequently the lower lateral lid) rub the cornea. Etiologies may be congenital, spastic, or cicatricial. This condition usually causes epiphora, blepharospasm, photophobia, conjunctivitis, purulent discharge, corneal vascularization, pigmentation and ulceration, if not surgically treated. Congenital entropion commonly affects dogs and is frequently hereditary in some breeds, whereas cats are uncommonly affected. A predilection for the Persian breed to present primary entropion has been suggested. The authors report two cases of entropion in Persian cats referred to the Ophthalmology Section of Veterinary College of São Paulo State University - UNESP, Jaboticabal - SP / Brazil. First case: a male Persian cat, 2 years old, with a history of bilateral ocular irritation and purulent discharge for 8 months. Ophthalmic examination revealed epiphora, blepharospasm, photophobia, bilateral entropion affecting the whole length of the lower eyelids, conjunctivitis and purulent discharge. Second case: a male Persian cat, 1 year old, with a history of bilateral ocular irritation and purulent discharge for 3 weeks. At ophthalmic examination the animal was presenting epiphora, blepharospasm, photophobia, bilateral entropion affecting the whole length of the lower lids, conjunctivitis, purulent discharge, corneal vascularization, superficial ulceration and edema. The entropion persisted after topical anaestesia in both cats. Surgical treatment was similar in both cases, based on the modified Holtz-Celsus procedure. Grid keratotomy procedure was also performed in the second case. Both cats had a satisfactory clinic evolution which was confirmed few days after surgery.

O entrópio é caracterizado por uma inversão da margem palpebral, na qual os cílios e os pêlos da pálpebra (freqüentemente a porção lateral da pálpebra inferior) atritam a córnea. A etiologia desta condição pode ser congênita, espástica ou cicatricial. Esta doença usualmente causa epífora, blefarospasmo, fotofobia, conjuntivite, secreção purulenta, vascularização, pigmentação e ulceração corneanas, se não for tratada cirurgicamente. O entrópio congênito comumente afeta cães e freqüentemente é hereditário em algumas raças, enquanto que os gatos raramente são acometidos. Uma predisposição da raça Persa tem sido sugerida. Os autores relatam dois casos de entrópio felino encaminhados ao Setor de Oftalmologia da Faculdade de Ciências e Veterinárias da Universidade Estadual Paulista - UNESP, Jaboticabal - SP / Brasil. Primeiro caso: felino macho, da raça Persa, com dois anos de idade e histórico de irritação ocular bilateral e secreção purulenta durante 8 meses. Ao exame oftálmico, observou-se epífora, blefarospasmo, fotofobia, entrópio bilateral, o qual afetava toda a extensão das pálpebras inferiores, conjuntivite e secreção purulenta. Segundo caso: felino macho, da raça Persa, com 1 ano de idade e histórico de irritação ocular bilateral e secreção purulenta durante 3 semanas. Ao exame oftálmico, o animal apresentava epífora, blefarospasmo, fotofobia, entrópio bilateral, o qual afetava toda a extensão das pálpebras inferiores, conjuntivite, secreção purulenta, vascularização corneana, ulceração superficial e edema. O procedimento cirúrgico empregado foi similar em ambos os casos baseando-se na técnica de Holtz-Celsus modificada. A ceratotomia em grade foi realizada no segundo caso. Os gatos obtiveram uma evolução clínica satisfatória, confirmada poucos dias após a cirurgia.
Entrópio primário em gatos persas
Keywords: eyelids; entropion; cats; pálpebras; entrópio; gatos